Host Phenology and Geography as Drivers of Differentiation in Generalist Fungal Mycoparasites - Pintye, Alexandra (PLoS One, 2015)
The question as to why parasites remain generalist or become specialist is a key unresolved question in evolutionary biology. Ampelomyces spp., intracellular mycoparasites of powdery mildew fungi, which are themselves plant pathogens, are a useful model for studies of this issue. Ampelomyces is used for the biological control of mildew. Differences in mycohost phenology promote temporal isolation between sympatric Ampelomyces mycoparasites. Apple powdery mildew (APM) causes spring epidemics, whereas other powdery mildew species on plants other than apple cause epidemics later in the season. This has resulted in genetic differentiation between APM and non-APM strains. It is unclear whether there is genetic differentiation between non-APM Ampelomyces lineages due to their specialization on different mycohosts. We used microsatellites to address this question and found no significant differentiation between non-APM Ampelomyces strains from different mycohosts or host plants, but strong differentiation between APM and non-APM strains. A geographical structure was revealed in both groups, with differences between European countries, demonstrating restricted dispersal at the continent scale and a high resolution for our markers. We found footprints of recombination in both groups, possibly more frequent in the APM cluster. Overall, Ampelomyces thus appears to be one of the rare genuine generalist pathogenic fungi able to parasitize multiple hosts in natural populations. It is therefore an excellent model for studying the evolution of pathogens towards a generalist rather than host-specific strategy, particularly in light of the tritrophic interaction between Ampelomyces mycoparasites, their powdery mildew fungal hosts and the mildew host plants.